The Effect of Cash Turnover and Accounts Receivable Turnover on Profitability of Food and Beverage Companies on the IDX - I Wayan Yoga Mila Pratama; I D M Mahayana; I M S A Jaya (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
This research was conducted because of the discrepancy between the theory of cash turnover, receivables turnover and profitability with the existing conditions in food and beverage companies on the IDX in 2016-2020. The purpose of this study was to determine the effect of partially and simultaneously cash turnover, accounts receivable turnover on profitability. The independent variables in this study are cash turnover and receivables turnover, the dependent variable in this study is profitability as measured by Return On Assets (ROA). The results show that there is a positive and significant effect between cash turnover on company profitability, then there is no effect There is a significant relationship between accounts receivable turnover on profitability and there is a positive and significant effect between cash turnover and accounts receivable turnover simultaneously on the company's profitability.